Razão e Proporção: Uma proposta de ensino explorando problemas do cotidiano - Priscilla Delatorre (2021)
This work aims to give meaning to the teaching of reason and proportion to students of the 7th year of Elementary School, using as a pedagogical tool the significant learning associated with technological resources that are increasingly present in the daily lives of students. In view of the transformations that our society has been facing over time, such changes must also be admitted in the educational scenario. The teacher as well as the school should accompany these transitions searching methods and strategies for the teaching-learning process is meaningful to the student. Thus, some activities are proposed using technological resources articulated with the students' daily lives, as it is believed that the process of memorization and learning occurs much more efficiently. Keywords: Reason and Proportion; Meaningful learning; Technological resources.